Physical activity and health in children (Portuguese Journal of Family Medicine and General Practice, 2004)
The child has a natural tendency to compare and compete with themselves and others. The game is so big motivating factor of the child. But as it renders their physical and sensorial Importance of training adaptation to the characteristics and biological age of the child. The medical examination of fitness sports such as opportunity assessment and orientation of physical exercise and sport safely. Asthma, heart murmurs, diabetes, epilepsy, scoliosis, are some of the common problems at this age, and being controlled, should not be grounds for exclusion from sport. Rather, exercise and sport give a good contribution to the health gains these children.